2022
DOI: 10.1186/s12865-022-00501-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum IL-2, IL-4, IL-5 and IL-12p70 levels in AChR subtype generalized myasthenia gravis

Abstract: Background Myasthenia gravis (MG) is an autoimmune disorder affecting neuromuscular junctions. Cytokines play important roles in facilitating the immune response and augmenting the pathogenic antibody production. The current study aims to sensitively characterize the serum levels of cytokines with very low concentration in generalized MG (gMG). Methods Using ultrasensitive single-molecule arrays (SIMOA), we measured serum IL-2, IL-4, IL-5 and IL-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Some studies found a less pronounced interferon alpha response in patients with severe disease than in those with mild disease 36,37 , another study reported persistently higher interferon alpha and lambda levels in patients with severe disease than in those with moderate disease 38 , and yet another study found no association between interferon alpha levels and disease severity 39 . These findings highlight the critical importance of highly sensitive and robust assays in exploring the low-abundance portion of the proteome that is enriched for important cytokines, such as interferons 40 .…”
Section: Discussionmentioning
confidence: 92%
“…Some studies found a less pronounced interferon alpha response in patients with severe disease than in those with mild disease 36,37 , another study reported persistently higher interferon alpha and lambda levels in patients with severe disease than in those with moderate disease 38 , and yet another study found no association between interferon alpha levels and disease severity 39 . These findings highlight the critical importance of highly sensitive and robust assays in exploring the low-abundance portion of the proteome that is enriched for important cytokines, such as interferons 40 .…”
Section: Discussionmentioning
confidence: 92%
“…Some studies found a less pronounced interferon alpha response in patients with severe disease than in those with mild disease 41,42 , another study reported persistently higher interferon alpha and lambda levels in patients with severe disease than in those with moderate disease 43 , and yet another study found no association between interferon alpha levels and disease severity 28 . These findings highlight the critical importance of highly sensitive and robust assays in exploring the low-abundance portion of the proteome that is enriched in important cytokines, such as interferons and IL4 44 .…”
Section: Discussionmentioning
confidence: 92%
“…In respect to the T cell compartment, in previous studies of EAMG, increased numbers of IL17 producing CD4 T cells were detected in the blood of EAMG mice [ 28 ]. In humans, CD4 T cells display increased production of IL4, IL17 and IL21 [ 29 , 30 ] and increased serum levels of these cytokines were detected [ 31 ]. In the context of EAMG, this dysregulated T cell response could create an inflammatory milieu conducive to the generation of antibody-producing B cells.…”
Section: Discussionmentioning
confidence: 99%